Grain Boundary Analysis of the Garnet-Like Oxides Li7+X−YLa3−XAXZr2−YNbYO12 (A = Sr or Ca) - Ohta, Shingo; Kihira, Yuki; Asaoka, Takahiko (Frontiers in Energy Research, 2016)
Garnet-like oxides having the formula Li7+X-YLa3-XAXZr2-YNbYO12 (A = Sr or Ca) were synthesized using a solid-state reaction and their bulk and grain boundary resistivities were assessed by AC impedance measurements. A difference in grain boundary resistivity was identified between the Sr and Ca materials and so the grain boundaries were examined using electron probe microanalysis (EPMA). The difference in the grain boundary resistivities was attributed to the core-shell structure of the Sr-substituted samples. In contrast, the Ca-substituted materials exhibited accumulations of impurities at the grain boundaries.